2012
DOI: 10.1186/1471-2407-12-241
|View full text |Cite
|
Sign up to set email alerts
|

Advanced non-small cell lung cancer in patients aged 45 years or younger: outcomes and prognostic factors

Abstract: BackgroundLung cancer in young patients (less or equal to 45 years) is uncommon and has clinical characteristics different from that in older patients. We investigated the outcomes and prognostic factors of young patients with advanced non-small cell lung cancer (NSCLC).MethodsFrom January 2000 to December 2009, we enrolled patients aged ≤45 years and diagnosed with stage IIIB or IV NSCLC. Their clinical data, including age, gender, performance status, histologic types, disease stages, laboratory data at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 46 publications
4
66
1
1
Order By: Relevance
“…When compared to other studies, our results show that certain clinical variables were consistently associated with survival, including age < 50 as well as gender and stage [3,6,11]. In a SEER analysis, five-year overall survival was significantly better in a group younger than 50 years of age (16.1% vs. 13.4%; P < .001), principally as a result of better survival in patients with presumably curable (localized or early stage) disease (48.7% vs. 35.4%; P < .001) [7].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…When compared to other studies, our results show that certain clinical variables were consistently associated with survival, including age < 50 as well as gender and stage [3,6,11]. In a SEER analysis, five-year overall survival was significantly better in a group younger than 50 years of age (16.1% vs. 13.4%; P < .001), principally as a result of better survival in patients with presumably curable (localized or early stage) disease (48.7% vs. 35.4%; P < .001) [7].…”
Section: Discussionsupporting
confidence: 51%
“…There have been numerous papers focused on young NSCLC patients, each with varying definitions of "young" [5][6][7][8]. Some of these studies attempted to compare outcomes between younger and older NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these prognostic factors, PS, weight loss, and the number of prior regimens played a significant prognostic role for OS in our study. In two recent retrospective studies, an ECOG PS of 2 or more, elevated serum LDH, and the absence of skin rash (Kim et al, 2010), as well as low BMI, stage IV disease, anaemia at diagnosis, and male gender (Hsu et al, 2012), were shown to be adverse prognostic factors for OS. Unlike these previous studies, the presence of an intra-abdominal metastasis was a negative prognostic factor for survival in patients with metastatic NSCLC treated with erlotinib in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, these analyses included only patients receiving first-line chemotherapy and cytotoxic therapy (Massarelli et al, 2003). Few reports have studied the prognostic factors for patients with NSCLC receiving second-or even third-line targeted therapies (Massarelli et al, 2003;Hsu et al, 2012). Our scoring system includes clinical factors instead of molecular markers.…”
Section: Discussionmentioning
confidence: 99%